Universal COVID-19 pre-procedural swabs in children in a developing country: A comparison of findings over two transmission waves. (28th September 2022) - Tan, Chee Yang; Theseira, Amelia Marie; Ahmad Zubaidi, Syukri; Atiya, Nadia; Sanmugam, Anand; Singaravel, Srihari; Nah, Shireen Anne
Aim: The Coronavirus disease (COVID-19) pandemic has strained healthcare systems worldwide. Some institutions have implemented additional precautionary measures such as pre-procedural swabbing (PPS) to reduce transmission in patients and healthcare workers. We evaluate our experience with universal pre-procedural screening for COVID-19 in low-risk pediatric patients. Methods: We performed a retrospective review of patients aged 18 years and below who underwent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) real-time reverse transcription-polymerase chain reaction (rRT-PCR) assay swabs in our center over two waves (1 st May 2020 to 31 st July 2020 and 1 st April 2021 to 30 th June 2021). We included patients who underwent rRT-PCR for SARS-CoV-2 prior to any procedures requiring general anesthesia and were deemed low risk for COVID-19 according to our institutional screening criteria. All study patients were followed up for 14 days post-procedure. Results: Of 2065 swabs done for patients aged 18 years and below during the study period, 645 (31.2%) were pre-procedural swabs. Patients were aged 4.2 years (median, interquartile range: 1.6 years–9.8 years). Two patients (0.3%) tested positive for COVID-19 by PPS, detected during Period 2 – both had risk criteria which were overlooked by healthcare workers. Within 14 days post-procedure, 10 patients had unscheduled readmissions and 15 required repeat rRT-PCR, all of which were negative. Conclusions: In patients deemed low risk for COVID-19 infection according to our screening criteria, routine pre-procedural swabbing returns a low positive rate. Our findings can guide screening protocols at institutions that provide surgical services during the COVID-19 pandemic.